สาระเนื้อหาทางบวกและลบ การสร้างภาพในใจสถานภาพทางเศรษฐกิจและสังคมและการระลึกจริยธรรมของเด็ก - วชิราพร อัจฉริยโกศล (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
Factors involving in teaching and learning about ethics have being long paid attention to. The present study was designed to investigate whether a) the presentation of positive and negative types of information, b) inducing imagery in children, and c) the socio-economic status of children had any effect upon the children's learning about and recalling ethics. There were four aspects of ethics: honesty, diligence, responsibility, and discipline. The interactive effects of these factors on the children's recall of ethics was also examined. 384 children, 192 boys and 192 girls, investigated in this study were third graders with an average age of eight years. Studies have shown that the children in this age group can form mental images (Pressley, 1976; Piaget and Inhelder, in Paivio, 1979; Maher and Sullivan, 1982). There were 192 children from families with low socio-economic status and another 192 children from families with high socio-economic status.A 2x2x2 factorial design was employed. By design, there were four different treatments: a) positive information/slide-tape and imagery, b) positive information/slide-tape, c) negative information/slide-tape and imagery, and d) negative information/slide-tape. The two socio-economic status groups of 192 children, were each randomly assigned to one of the four treatments. Therefore, there were a total of eight groups of children comprised by four experimental groups and four control groups. There was an equal number of boys and girls in each group. The results of the study were as follows: 1) The three-way interaction was found no significant. Only one of the three two-way interactions, types of information by imagery, was found significant at .01 level. 2) The slide-tape and imagery with negative information was the most effective treatment for both low and high socio-economic status groups. For the low socio-economic status group, the slide-tape was found superior to the slide-tape and imagery treatment whenit was presented with positive information. For the high socio-economic status group, the slide-tape and the slide-tape and imagery treatments were equally effective when the information presented was positive information. 3) The analysis resulted in significant main effects, at .01 level, for two of the three independent variables: High socio-economic status children scored higher than low socio-economic status children; negative information was more effective than positive information.